Metabolic Syndrome and Serum Liver Enzymes in the General Chinese Population - Chen, Shuang (Int J Environ Res Public Health, 2016)
Background: The aim of this study was to evaluate the associations between alanine aminotransferase (ALT) and aspartate aminotransferase (AST) with metabolic syndrome (MetS) in the general Chinese population. Methods: This study was a multicenter, cross-sectional study which was conducted in rural areas of China from the 2012 to 2013 Northeast China Rural Cardiovascular Health Study (NCRCHS), and 11,573 adults with complete data were included in our final analysis. Elevated ALT and AST levels were defined as >40 U/L. Serum ALT and AST levels within the reference range were divided into quartiles, and their associations with MetS were evaluated by logistic regressions. Results: A total of 7.4% and 3.5% participants had elevated serum ALT and AST levels, respectively. The prevalence of MetS was 37.3% in males and 45.8% in females. After adjusting for potential confounders, we found ALT level elevation, even within the reference range, was independently associated with MetS. The odds ratio (OR) values of MetS in the ALT quartiles 2–4 groups within the reference range were 1.113 (95% CI: 1.019–1.280), 1.375 (95% CI: 1.212–1.560), 1.878 (95% CI: 1.650–2.138) compared with the ALT quartile 1 group, and OR in the elevated ALT group was 3.020 (95% CI: 2.496–3.653). Positive relationship for MetS was also observed in elevated AST group (OR: 1.689, 95% CI: 1.314–2.171), but within the reference range, the AST level was not associated with MetS. Conclusions: Serum ALT level, even within the reference range, was significantly associated with MetS. However, only elevated AST levels above 40 U/L was positively associated with MetS. Within the reference range, we did not find a relationship between AST levels and MetS.